β-Cyclodextrin conjugated magnetic, fluorescent silica core-shell nanoparticles for biomedical applications - Md. Badruddoza , Abu Zayed; Rahman , Md. Taifur; Ghosh , Sudipa; Hossain , Md. Zakir; Shi , Jizhong; Hidajat , Kus; Uddin, Mohammad Shahab (Elsevier Ltd., 2013)

(untitled)
We present synthesis of highly uniform magnetic nanocomposite material possessing an assortment of important functionalities: magnetism, luminescence, cell-targeting, and hydrophobic drug delivery. Magnetic particle Fe 3O4 is encapsulated within a shell of SiO2 that ensures biocompatibility of the nanocomposite as well as act as a host for fluorescent dye (FITC), cancer-targeting ligand (folic acid), and a hydrophobic drug storage-delivering vehicle (β-cyclodextrin). Our preliminary results suggest that such core-shell nanocomposite can be a smart theranostic candidate for simultaneous fluorescence imaging, magnetic manipulation, cancer cell-targeting and hydrophobic drug delivery.